Research Progress on the Immunogenicity and Regeneration of Acellular Adipose Matrix: A Mini Review - Liu, Kaiyang; He, Yunfan; Lu, Feng (Frontiers in Bioengineering and Biotechnology, 2022)
Acellular adipose matrix (AAM) has received increasing attention for soft tissue reconstruction, due to its abundant source, high long-term retention rate and in vivo adipogenic induction ability. However, the current decellularization methods inevitably affect native extracellular matrix (ECM) properties, and the residual antigens can trigger adverse immune reaction after transplantation. The behavior of host inflammatory cells mainly decides the regeneration of AAM after transplantation. In this review, recent knowledge of inflammatory cells for acellular matrix regeneration will be discussed. These advancements will inform further development of AAM products with better properties.